THEARISINGSTAGESOFDISLOCATIONOFMARKETSTRUCTUREIN COLD-CARBONSTEEL - Vakulenko, I. O.; Gryshchenko, M. A.; Gryshchenko, M. M. (Science and Transport Progress, 2008)
The article is devoted to explanation of the evolutional process of dislocation cell structure formation during the plastic deformation of carbon steel.